PERAN KEPALA SEKOLAH DALAM MENINGKATKAN PEMASARAN JASA PENDIDIKAN DI SMA NEGERI 2 MUARA WAHAU - Hermanto, Heri; Ifendi, Mahfud (MPI STAI Sangatta Kutai Timur, 2024)
Education is seen as a tactical instrument to improve people's standard of living. Leadership is an important component in the management of educational institutions because it produces human resources through internal education who are ready and competent to compete in both local and global contexts. Therefore, to meet society's increasing demands, educators must actively present themselves as qualified professionals. One of them is that the school principal in carrying out his function is managing the marketing activities of educational services for educational institutions by using good strategies to convince stakeholders and the community or customers. The approach used in this research is a qualitative approach with a case study type of research, in which the author investigates and understands directly what happens in the field. The data collection techniques used by the author are observation, interviews, and documentation. This research was conducted at SMA Negeri 2 Muara Wahau. The data analysis technique used by the author was the Miles & Huberman model starting from data condentation, data display, and drawing conclusions and verification. The results of this research are the principal at SMA Negeri 2 Muara Wahau's improvement of marketing educational services using three stages. The first is to analyze the strategy, this is done by first identifying the market with market segmentation, market targeting, and market positioning. Next, the school principal plans using a marketing mix approach, and the last is implementing the existing plan, namely offering good products, effective and efficient promotions, qualified and competent teaching staff, and adequate infrastructure.